Information highway : the interstate highway system for computer networks. - FORCHT, Karen A. (1994)
Presents a basic definition of the information highway, including security, hardware and software, and discusses future ramifications. Identifies the four main parties involved as the cable companies, telephone companies, Internet and the policy-makers in Washington. Specifies a number of legislative issues involved.